A decisão de compra de vestuário no varejo de baixa rendab: a influência das características do produto e da apresentação na loja - Muraro, Marco Luiz Clasen (2007)
The intended contribution of this study is to provide a better understanding of the behavior of low-income consumers regarding the attributes of clothing products assessed when deciding on a purchase, as well as the influence of the various ways of displaying products in a store. Through group discussions and interviews with salespeople, we have analyzed the aspects of clothing products most evaluated upon purchase, such as, appearance, color, fabric, fit, etc. We have also analyzed the client’s perception regarding the different ways of displaying products in a store, including store windows , mannaquins, walls, exhibiting tables, floor equipment, among others. Through fashionable clothes, consumers express their individuality and, frequently make use of them to promote social inclusion, especially when it comes to low-income consumers. Fashion is also a way to express distinction between social classes and, it is often exercised as a way to affirm one’s identity. The study focused on the Riachuelo store located in the Ibirapuera Shopping Mall, due to its importance as a unit to this Chain, concerning the image that it has established for the general public of São Paulo City. Our object of study was clients with demographic profiles whithin the avarage of the clients of the Ibirapuera Mall store who usually purchase products with the AK and Anne Kanner brands. The brands mentioned belong to the chain and are targeted at women between 26 and 45 years old. Results indicate that the main aspects of the in-store decision making process when choosing a product , are physical attributes such as style and color. Although these attributes are defining, they are not decisive. Once products have been chosen, customers depend on how well they fit, regarding size, shape, and comfort. Only if these criteria are met will the purchase be decided on. Therefore, most of the time, the purchase decision will happen after the clothes have been tried on. In regard to the styles on display , the study also shows that low-income consumers need information and guidance concerning fashion , which means that the more the visual information is able to help them, through exhibitions of complete outfits, as in store windows, mannaquins and walls, the more easily the consumer will make a decision. Store windows appear as a defining factor as a point of attraction, followed followed by exhibitions on mannequins and walls as the as the main help resources in the decision making process. This study has yielded a better understanding of the store clients, and it should be used to achieve a higher accurateness in the development of new collections and in their presentation to the chosen segment. This work also meant to contribute to the improvement of the knowledge about the behavior of low-income consumers regarding the purchase decision of fashion clothing items.